Da concepção do bullying ao fenômeno da violência como manifestação da alienação - uma análise onto-histórica - Mota, Kildilene Carvalho Matos (2015)
This work aims to demonstrate, in the light of Marxian / Lukacsian ontology, one of the faces that violence takes in the context of structural crisis of capital: bullying, english word without corresponding to the Portuguese language. We understand that our analysis must start from the understanding of the pillar structure society in which we live which is the capital-labor relation to the production. For this reason we will launch hand of the following authors: Engels (1979), which deals with the theory of violence; while Marx (2008) analyzes the estranged character of the work, this estrangement that unfolds including about what this thinker named autoalienação (on the individual and their relationship with the human race); Mészáros (2006), which took upon itself the task of analyzing the characteristics of capitalist society under the unprecedented crisis of this system, a crisis that exacerbates the problems of humanity, which therefore accentuates the manifestations of violence. These authors demonstrate that the analyzes undertaken by various authors are limited, according to which bullying refers to violent acts without apparent motivation, practiced among students in schools, which phenomenon has been studied since the late 1970 worldwide. Silva (2010) states that the phenomenon is a public health problem; Fante and Pedra (2008) claim that it is necessary to recognize the phenomenon in order to differentiate it from other forms of violence. Contrary to the analysis of these authors, we understand that bullying is not actually a new phenomenon, because in its essence is anchored in historical and social conditions whose understanding is provided by the Marxian legacy. Finally, it is only this legacy that allows us to understand the cell who chairs the specific sociability, merchandise. It is from this cell we can understand the process of dehumanization of men themselves, of which bullying is expression.